Testing Interaction Effect of Firm Size on Net Trade Credit: Another Perspective from Indonesian Capital Market - Andre; Wendy (Ilomata International Journal of Management, 2024)
This research takes a different perspective by only using trade credit from third-party transactions. This research uses primary consumer sector corporates listed on the Indonesia Stock Exchange with a purposive sampling method, obtaining a total of 235 data points. The results of this study indicate that capital structure and efficiency positively affect net trade credit. Conversely, firm age has a negative affect net trade credit When interacted with firm size, the firm age significantly has a positive effect on net trade credit. Meanwhile, efficiency consistently has a positive effect on net trade credit. The interaction effect of firm size on these factors tends to weaken. This study provides implications for the importance of using trade credit from third parties as creditworthiness, as well as further evidence regarding formal financing in the redistribution theory in Indonesian corporations.